Portrait en clair-obscur de la Vaison tardive l'état du forum dans l'Antiquité tardive = A chiaroscuro portrait of late Vaison : the forum in Late Antiquity - Michel d'Annoville, Caroline 1966-; Mignon, Jean-Marc (2023)
The recent excavation of the forum of Vaison-la-Romaine (Vaucluse) offers the opportunity to wonder of the future of the ancient city and its public monuments during Late Antiquity. This monumental complex, already partly uncovered in the 1940s by Canon Joseph Sautel and since the subject of an erudite investigation, was thus more widely observed as part of an excavation scheduled between 2011 and 2015. During this operation, levels of dismantling and occupation attributed to Late Antiquity were identified, allowing, despite some imprecisions regarding dating and new uses of spaces, to initiate a reflection on urban topography and the management of the heavy ancient monumental heritage, in a city that is transforming, in a context of Christianization of landscapes.
Keywords: Städtebau; Spätantike; Vaison-la-Romaine